Comprehensive analysis of parotid mass: A retrospective study of 369 cases. Issue 2 (April 2018) - Comoglu, Senol; Ozturk, Erkan; Celik, Mehmet; Avci, Hakan; Sonmez, Said; Basaran, Bora; Kiyak, Erkan
Abstract: Objective: To present the results of patients who underwent superficial or total parotidectomy because of parotid gland tumors in our tertiary care clinic. Methods: The data of 362 patients who underwent parotid surgery from January 2008 to November 2015 were collected and analyzed in demographic, histopathological features, and complications. Results: Three hundred sixty-nine cases (performed in 359 patients) were analyzed and we assessed complications of parotid surgery such as transient or permanent facial paralysis and Frey's syndrome. Pleomorphic adenomas and Warthin's tumors consisted 74% of all parotid gland tumors. These tumors were generally located in the superficial lobe and tail of the parotid gland (81%). Also, tumor size in the positive surgical margin group was larger than in the negative surgical margin group ( p = 0.012). Conclusions: Most of parotid gland tumors are benign. However, the frequency of malignancy increases in deep lobe of parotid gland. High grade malignant tumors have more tendency to have positive surgical margin during surgery, and facial paresis preoperatively.